Ovarian characteristics, serum hormone concentrations, and fertility in lactating dairy cows in response to equine chorionic gonadotropin - Pulley, Stephanie Leeann; Wallace, L.D.; Mellieon, H.I.; Stevenson, Jeffrey S. (Kansas Agricultural Experiment Station and Cooperative Extension Service, 2012)
The objective of this study was to evaluate the effects of equine chorionic gonadotropin (eCG) on various characteristics associated with an effective timed artificial insemination (AI) protocol in lactating dairy cows. Cows (n = 121) in a single herd were treated with 2 injections of prostaglandin F2α (PGF2α) 14 days apart (Presynch), with the second injection administered 11 days before the onset of a timed AI protocol. Cows received either saline or 400 IU eCG concurrent with the PGF2α injection of the Ovsynch protocol (injection of gonadotropinreleasing hormone or GnRH, 7 days before and 48 to 56 hours after PGF2α with insemination occurring 12 to 16 hours after the second GnRH injection). Blood samples were collected during the study to monitor serum changes in progesterone and estradiol in order to determine if eCG would facilitate increased estrual activity, improved ovulatory response, and enhanced postovulatory luteal function. Administration of eCG tended to increase the number of corpora lutea (CL) and on days 9 and 16 after PGF2α, corresponding to days 6 and 13 postovulation, but the volume of the luteal tissue was less than that in the control. Timed AI pregnancy rates did not differ between eCG (36.9%) and control cows (41.8%). We concluded that use of eCG provided no profertility advantages to dairy cattle when programmed for a timed insemination at first service.
Dairy Research, 2010 is known as Dairy Day, 2010
Keywords: Dairy; Corpus luteum; Equine chorionic gonadotropin; Follicle; Progesterone; timed artificial insemination (AI)